(untitled) (European Journal of Social Science Education and Research, 2017)
Child maltreatment is a phenomenon which has a high impact on child health, causing serious disruptions in the development of the child and, in some extreme cases, their death. Thereby, cooperation and coordination among services and professionals is a crucial factor affecting the effective assistance of children who have been victims or witnesses of violence. However, the intervention in cases of child maltreatment is a complex issue that faces specific difficulties in every step of the intervention process which also may depend on each country’s features and its protection system. Specifically, this paper is focused on the most challenging issues that different professionals of child protection services, such as social workers, health-care specialists and psychologists among others, face in Estonia, Finland, Slovenia and Spain, with particular emphasis in professional's training needs. A methodological triangulation, combining desk research, focus groups and questionnaires have been used to obtain a broader and deeper perspective of the objective of the study. The analysis developed in this paper has shown that coordination among professionals and system, legal procedures, attitudes, training issues and lack of resources can be understood as the main challenges that professionals have to face. As for professionals’ training needs, the results have shown that they were different in each country. This fact might be related to idiosyncratic features and configuration of the child protection systems and the kind of potential users that they have.